2021
DOI: 10.1097/md.0000000000024723
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of gamma-glutamyl transpeptidase-to-platelet ratio (GPR), red cell distribution width (RDW), aspartate aminotransferase-to-platelet ratio index (APRI), and the fibrosis-4 index (FIB4) compared with liver biopsy in patients with drug-induced liver injury (DILI)

Abstract: This study objected to evaluate the accuracy of the gamma-glutamyl transpeptidase-to-platelet ratio (GPR), aspartate aminotransferase-to-platelet ratio index (APRI), red cell distribution width (RDW), and fibrosis-4 index (FIB4) index, compared with liver biopsy (LB), in predicting the severity of inflammation in drug-induced liver injury (DILI) patients. We evaluated patients with DILI who were followed at the First Hospital of Jilin University and underwent LB. Accuracy of each method was analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…In fact, all scores have been developed for special hepatic patient groups [27][28][29]55,56], which might lead to the under-or overestimation of the clinical status of a patient when applying the scores for other etiologies. However, the use of these scores in different settings has been tested by others [30][31][32][33]57].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, all scores have been developed for special hepatic patient groups [27][28][29]55,56], which might lead to the under-or overestimation of the clinical status of a patient when applying the scores for other etiologies. However, the use of these scores in different settings has been tested by others [30][31][32][33]57].…”
Section: Discussionmentioning
confidence: 99%
“…The actual AST, upper limit of normal of AST and platelet count are required for the calculation [29]. Beside the validated application areas, NFS, FIB-4, and APRI were tested as predictive models for the occurrence of cirrhosis in the general population [30], esophageal varices in hepatocellular carcinoma (HCC) patients [31], as well as mortality among COVID-19 patients [32] or inflammation in drug-induced liver injury [33].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, liver fibrosis caused by these chronic diseases is treated or even reversed because of the cure of these chronic diseases, that is, the removal of the cause. In addition, autoimmune hepatitis (AIH), drug-induced liver injury (DILI), non-alcoholic steatohepatitis (NASH), and alcoholic steatohepatitis (ASH) are also the main causes of liver fibrosis ( Mueller et al, 2010 ; Valera et al, 2011 ; Tacke and Weiskirchen, 2021 ; Wan et al, 2021 ). It has been reported that fibrosis and histological activity index of 54 AIH patients with liver fibrosis who received immunosuppressive therapy decreased significantly ( Valera et al, 2011 ).…”
Section: Progress In the Treatment Of Liver Fibrosismentioning
confidence: 99%
“…Aspartate aminotransferase (AST) -platelet ratio index (APRI) has been used in many studies to diagnose liver injury (5). Although the APRI score has been found to be a reliable predictor of fibrosis in previous studies (6), it remains unclear whether it is also a strong predictor for ICP.…”
mentioning
confidence: 99%